Relationship between intravascular ultrasound parameters and fractional flow reserve in intermediate coronary artery stenosis of left anterior descending artery: Intravascular ultrasound volumetric analysis. Issue 3 (23rd October 2013) - Yang, Hyoung‐Mo; Tahk, Seung‐Jea; Lim, Hong‐Seok; Yoon, Myeong‐Ho; Choi, So‐Yeon; Choi, Byoung‐Joo; Jin, Xiong Jie; Hwang, Gyo‐Seung; Park, Jin‐Sun; Shin, Joon‐Han
<x xml:space="preserve">Abstract</x> Objectives The objective of this study was to assess the relationship between intravascular ultrasound (IVUS) parameters, including volumetric analysis, and fractional flow reserve (FFR). Background Although it is known that coronary atherosclerosis burden measured by IVUS volumetric analysis is related with clinical outcomes, its relationship with functional significance remains unknown. Methods Both IVUS and FFR were performed in 206 cases of intermediate stenosis of the left anterior descending artery (LAD). Myocardial ischemia was assessed by FFR and maximal hyperemia was induced by continuous intracoronary adenosine infusion. FFR < 0.80 was considered as significant inducible myocardial ischemia. We performed standard IVUS parameter measurements and volumetric analyses. IVUS parameter comparison was performed in the presence (n = 90) or absence (n =116) of significant myocardial ischemia. Results Lesions with minimal lumen area (MLA) ≥ 4.0 mm2 had FFR ≥ 0.80 in 91.4% of cases, while 50.9% of lesions with MLA < 4.0 mm2 had FFR < 0.80. The independent predictors of FFR < 0.80 were IVUS lesion length (odds ratio [OR]: 1.1, 95% confidence interval [CI] = 1.06–1.18, P < 0.001) and MLA significance according to the lesion location (OR: 7.01, 95% CI = 3.09–15.92, P = 0.001). FFR correlated with plaque volume (r = −0.345, P < 0.001) and percent atheroma volume (PAV) (r = −0.398, P < 0.001). Lesions with significant ischemia (FFR < 0.80) as compared to those with FFR > 0.80 were associated with larger plaque volume (181.8 ± 82.3 vs. 125.9 ± 77.9 mm3, P < 0.001) and PAV (58.9 ± 5.6 vs. 53.8 ± 7.9%, P < 0.001). Conclusions IVUS parameters representing severity and extent of atheromatous plaque correlated with functional significance in LAD lesions with intermediate stenosis. © 2013 Wiley Periodicals, Inc.